Making Teacher and Researcher Learning Visible: Collaborative Design as a Context for Professional Growth. Issue 1 (2nd January 2022) - Ko, Mon-Lin Monica; Hall, Allison; Goldman, Susan R.
Abstract: Collaborative design (co-design) involving practitioners and researchers is emerging as a productive context for addressing theoretical as well as practical issues of teaching and learning. Co-design affords learning opportunities for all participants, although the focus has typically been on teachers. In this study, the Interconnected Interactive Model of Professional Growth (IIMPG) serves as a conceptual tool for tracing professional growth pathways of teachers and researchers in co-design contexts. The IIMPG is illustrated through a case study of a teacher and a researcher during a multi-year co-design project. Interactional analyses of their co-design work indicated change in the roles of the teacher and the researcher, knowledge of science inquiry as text-based modeling, and strategies for supporting students in engaging in it. Four years later, the teacher and researcher collaborated in retrospective reflection on their co-design work. Analyses revealed increased awareness of the underlying principles governing the multiple components of the design and how these supported conceptual coherence and interconnected knowledge for students. The multiple lenses and timescales enabled new insights on when, how, and why people learn during collaborative design. The IIMPG served as a generative tool for capturing professional growth pathways for teachers and researchers over iterative co-design cycles.